2016
DOI: 10.1371/journal.pone.0161360
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Matrix Protein Inhibits Host Cell Transcription

Abstract: Measles virus (MeV) is a highly contagious virus that still causes annual epidemics in developing countries despite the availability of a safe and effective vaccine. Additionally, importation from endemic countries causes frequent outbreaks in countries where it has been eliminated. The M protein of MeV plays a key role in virus assembly and cytopathogenesis; interestingly, M is localised in nucleus, cytoplasm and membranes of infected cells. We have used transient expression of M in transfected cells and in-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…All of these findings accelerate our understanding of the potential functions of paramyxovirus M proteins. For the NDV M protein, one familiar function is the core role of the M protein in the assembly and budding of NDV [ 7 , 13 ], and another function is the hypothesized transcriptional inhibition of the M protein in the nucleus, which is analogous to the M proteins of human respiratory syncytial virus (HRSV) [ 37 ], vesicular stomatitis virus (VSV) [ 38 ] and MeV [ 39 ]. In recent years, although several studies have demonstrated that the interactions of the M protein with host proteins are crucial for the replication and pathogenicity of NDV [ 11 , 18 20 ], none of these host proteins are associated with nuclear proteins or the budding functions of the NDV M protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these findings accelerate our understanding of the potential functions of paramyxovirus M proteins. For the NDV M protein, one familiar function is the core role of the M protein in the assembly and budding of NDV [ 7 , 13 ], and another function is the hypothesized transcriptional inhibition of the M protein in the nucleus, which is analogous to the M proteins of human respiratory syncytial virus (HRSV) [ 37 ], vesicular stomatitis virus (VSV) [ 38 ] and MeV [ 39 ]. In recent years, although several studies have demonstrated that the interactions of the M protein with host proteins are crucial for the replication and pathogenicity of NDV [ 11 , 18 20 ], none of these host proteins are associated with nuclear proteins or the budding functions of the NDV M protein.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that M nuclear localization in some cytoplasmic RNA viruses, such as MeV and VSV, can inhibit host cell transcription independently of other viral components. For example, transiently overexpressed MeV M protein in plasmid-transfected cells binds to nuclear factors and inhibits in vitro transcription in a dose-dependent manner [ 39 ]. Other studies reported that the VSV M protein directly inhibits host cell transcription by inactivating host RNA polymerases I and II [ 44 ] and interacts with nuclear pore complexes to impair nuclear export of cellular mRNAs, which indirectly leads to a decrease and an increase in host cell and virus gene transcription, respectively [ 45 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the nuclear-cytoplasmic trafficking of the M protein is important for the replication process of Nipah virus (36) and NDV (37). Recently, it has been shown that the MV M protein can be located in the nucleus and inhibit host cell transcription (38). All these observations suggest that the MV M protein receives posttranslational modification in the nucleus for its proper functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that "General function prediction only" (group R, 58 DEPs), "Posttranslational modification, protein turnover, chaperones" (group O, 51 DEPs), and "Translation, ribosomal structure and biogenesis" (group J, 63 DEPs), "General function prediction only" (group R, 50 DEPs) represented the four largest groups in rSS1GFP group at 12 and 24 hpi, respectively ( Figure 6(a,b)). However, "Translation, ribosomal structure and biogenesis" (group J, 15 DEPs), "Signal transduction mechanisms" (group T, 12 DEPs), and "Translation, ribosomal structure and biogenesis" (group J, 16 DEPs), "Signal transduction mechanisms" (group T, 9 DEPs) were the largest four groups in rSS1GFP-M/NLSm group at 12 and 24 hpi, It has been reported that the M protein of several nonsegmented negative-sense RNA viruses (NNSVs) including HRSV, VSV and MeV has the ability to inhibit host cell transcription in various ways [7][8][9]. To determine whether the NDV M protein can inhibit cell transcription process, we mainly focused on the expression profiles of DEPs related to "Transcription" and "RNA processing and modification" according to the results of COG/KOG categories analysis.…”
Section: Annotation Analysis Of the Identified Depsmentioning
confidence: 99%